To the Question of Use of Historical Texts of G. F. Kvitka-Osnovyanenko in Modern Educational Literature on the History of Slobodska Ukraine. - Танцюра, Василь (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article highlights the role and significance of the historical works of G.F. Kvitka-Osnovyanenko in teaching compulsory courses and disciplines for the choice of students on the history of Sloboda Ukraine in higher education. The aim of the article is to highlight the information potential of the writer’s works on historical subjects, attracting the attention of scientists and teachers to his legacy. It is proved that the most informative potential is possessed by such works of the writer as “On the Slobodskiy Regiments”, “The Foundation of Kharkov. Ancient tradition”, “About Kharkov and district cities of the Kharkov province”, “Ukrainians”. The writer’s heritage has become a significant contribution to the study of the history of the region. The data collected and published by him were confirmed in historical studies of the following years, and some of the information is unique and almost serves as the only source on some issues. His works are saturated with both statistical materials and emotional sketches, attempts to convey the features of everyday life, language, psychology of behavior of the region’s inhabitants. Therefore, the potential for the use of his works in educational literature, and therefore in the framework of courses on regional and Ukrainian history, remains quite significant. Historians, firstly, have an emphasis on which evidence is unique, the only source of information. Secondly, the use of masterful descriptions from the writer’s works will make it possible to make the presentation of questions of the political, socio-economic and cultural history of the region more vivid and emotionally rich. Thirdly, we believe that providing them with a characterization in the educational literature, using the writer’s works at seminars and lectures, it is necessary to explain in detail the specifics of those fragments of texts containing the characteristics of Ukrainians, Slobozhans, Malorossovs national peculiarities, the presence of evaluations committed to Russia, etc. through the prism of self-identification of the population of the region and all Ukrainians lands in order to show its evolution in the XIX-XX centuries.